(untitled) (Theological Kronos, 2017)
The occurrence of multiple rape and dismemberment in middle of a holy book like the Bible generates mistrust, therefore by believers and even more by non-believers. The current article presents an approach from the narrative in chapter 19 of Judge´s book; there are been studied the characters that come into action and how are their actions. The article wants to show how the narrative is preparing the way to the Davidic monarchy and how it discredits the one of Saul.